Prospects for management strategies of invasive crayfish populations with an emphasis on biological control - Freeman, M.A.; Turnbull, J.F.; Yeomans, W.E.; Bean, C.W. (Wiley-Blackwell Publishing, Inc, 2010)
1. The white-clawed crayfish, Austropotamobius pallipes (Lereboullet), is the only freshwater crayfish indigenous to Great Britain and Ireland. It has a widespread, though declining distribution in England and parts of Wales but does not occur naturally in Scotland. 2. The North American signal crayfish, Pacifastacus leniusculus (Dana), is not native to Europe and was introduced to Britain in the 1970s. The signal crayfish out-competes the native white-clawed crayfish as it is larger and more aggressive. It is also responsible for the introduction and spread of crayfish plague, which has devastated white-clawed crayfish populations in Europe. 3. Signal crayfish populations are causing significant changes to the equilibrium of native. ora and fauna through increased grazing and predation pressures; they also contribute to habitat degradation through burrowing. 4. Manual removal of crayfish using traps and pond trials with biocides have met with moderate success in reducing crayfish numbers and containing populations. However, with new populations of signal crayfish being reported each year within the UK, there is now an urgent need to develop a strategy with which to eradicate or contain their spread. 5. Signal crayfish have populated many habitat types in the UK, each of which may require a different control strategy; hence no single strategy or universal solution is likely to be attainable. 6. Signal crayfish are susceptible to various biocides and microbial pathogens but significant scientific research will be required to develop safe biological control methods and integrated pest management (IPM) strategies to control these invasive organisms. Copyright (C) 2009 John Wiley & Sons, Ltd.